Mengelola Dan Mendidik Anak Dengan Hati : Managing And Educating Children With Love - Sofiul Imam ,MohammadLutfi (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2018)
Early Childhood Education (PAUD) aims to develop high-quality Indonesian children, namely children who grow and develop in accordance with their developmental level, so that they are optimally prepared to enter primary education and navigate adult life. Additionally, it also aims to help prepare children to achieve academic readiness in school. This aligns with the essence of character education, which is now being revitalized at all levels of education, from PAUD to higher education, namely implementing the process of forming good behavior and habits (habituation) in living a life that includes religious education, values education, character education, moral education, and personality education aimed at developing students' ability to make good and bad decisions, maintain what is good, and embody that goodness in their daily lives with all their heart. Pendidikan Anak Usia Dini (PAUD) bertujuan membentuk anak Indonesia yang berkualitas, yaitu anak yang tumbuh dan berkembang sesuai dengan tingkat perkembangannya, sehingga memiliki kesiapan yang optimal di dalam memasuki pendidikan dasar serta mengarungi kehidupan di masa dewasa. Selain itu, juga untuk membantu menyiapkan anak mencapai kesiapan belajar (akademik) di sekolah. Hal ini sesuai dengan esensi pendidikan karakter yang sekarang sedang kembali digalakkan di semua level pendidikan mulai dari PAUD sampai perguruan tinggi yaitu mengimplementasikan proses pembentukan perilaku dan kebiasaan yang baik (habituation) dalam menjalani kehidupan yang mencakup pendidikan agama, pendidikan nilai, pendidikan budi pekerti, pendidikan moral, pendidikan watak yang bertujuan mengembangkan kemampuan peserta didik untuk memberikan keputusan baik buruk, memelihara apa yang baik dan mewujudkan kebaikan itu dalam kehidupan sehari- hari dengan sepenuh hati